The concept of cone creation to treat isolated tricuspid valve dysplasia and the case of a double-orifice tricuspid valveCentral MessagePerspective - Andrea Giulio Quarti, MD; Francesco Dimitri Petridis, PhD; Valeria Francesca Mangerini, MD; Lucio Careddu, PhD; Emanuela Angeli, PhD; Gaetano Domenico Gargiulo, PhD (JTCVS Techniques)
Objectives: Isolated tricuspid valve dysplasia is a rare disease characterized by a wide spectrum of possible anomalies. We describe the use of the Cone concept to treat a patient with a double-orifice tricuspid valve with massive regurgitation and severe deficit of coaptation. Methods: Three adult patients with congenital non-Ebstein tricuspid valve anomaly characterized by severe coaptation deficiency underwent tricuspid valve repair applying the Cone technique. In particular, we describe the case of a symptomatic 21-year-old woman with a double-orifice tricuspid valve, with massive regurgitation and severe right ventricular dilatation. The tricuspid valve was transformed from a double-orifice valve into a single-orifice valve. The most superior orifice was opened, and the tissue surrounding the orifice was used to extend the leaflet of the inferior orifice. A Cone was created, and a ring annuloplasty was used to stabilize the result. Results: The patient was discharged home after 7 days with trivial residual tricuspid regurgitation and no significant antegrade gradient. The final coaptation height was 2.8 cm. The cardiothoracic ratio decreased from 0.77 to 0.59 after 2 months, and symptoms promptly improved. Conclusions: Over the past 2 years, we have applied the Cone creation concept to patients with a severely dysplastic tricuspid valve with excellent early results. One patient had a double-orifice tricuspid valve, and a Cone repair concept was adopted anyway. One orifice was sacrificed, and surrounding tissue was used to augment the leaflets of the other orifice. A Cone was created to improve central coaptation with a good initial result.